2023
DOI: 10.1161/jaha.123.030456
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Ambient Air Pollution Exposure and Risk of Out‐of‐Hospital Cardiac Arrest in Sweden: A Nationwide Case‐Crossover Study

Marcus Dahlquist,
Viveka Frykman,
Jacob Hollenberg
et al.

Abstract: Background Air pollution is one of the main risk factors for cardiovascular disease globally, but its association with out‐of‐hospital cardiac arrest at low air pollution levels is unclear. This nationwide study in Sweden aims to investigate if air pollution is associated with a higher risk of out‐of‐hospital cardiac arrest in an area with relatively low air pollution levels. Methods and Results This study was a nationwide time‐stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…While many of these factors operate through long-term accumulation of risk, factors that trigger myocardial infarctions in the short term, such as stress or air pollution, may contribute as well [ 32 , 33 ]. Research has shown that air pollution can indeed affect the risk of myocardial infarction within weeks, days and even hours of exposure to pollutants [ 34 36 ]. Even despite the comparatively lenient restrictions during the pandemic, Swedish air pollution levels decreased substantially.…”
Section: Discussionmentioning
confidence: 99%
“…While many of these factors operate through long-term accumulation of risk, factors that trigger myocardial infarctions in the short term, such as stress or air pollution, may contribute as well [ 32 , 33 ]. Research has shown that air pollution can indeed affect the risk of myocardial infarction within weeks, days and even hours of exposure to pollutants [ 34 36 ]. Even despite the comparatively lenient restrictions during the pandemic, Swedish air pollution levels decreased substantially.…”
Section: Discussionmentioning
confidence: 99%